Estrutura do dossel e acúmulo de forragem dos capins piatã e marandu sob pastejo com ovinos - Lima, Carla Lailane Dias de (2013)
The objective of this scientific work was to evaluate the tillering and mass production of Brachiaria brizantha Piatã and Marandu grasses with two statures of post-grazing. The experimental lineation was in factorial arrangement (2 pastures x 2 residue stature) with subplots (grazing cycle). The experimental period was from March to October of 2012. The target stature on pre-grazing was 50 cm and on post-grazing 15 and 25 for each cultivar. The following variables were analyzed: tiller population density, forage mass, morphological components, accumulation and accumulation rate. Three grazing cycles were obtained. Marandu grass presented larger forage mass on pre-grazing and lower stem production than piatã grass. No difference was observed between the two cultivars regarding the leaf blade production. There was no difference on forage mass, leaf blade, stem, and dead material production between the two statures of post-grazing. The pastures managed at 25 cm presented accumulation rate compared to those with 15 cm. Concerning the accumulation rate on the two cultivars, piatã and marandu grasses, Marandu grass presented higher amount than the piatã grass, and also presented higher values on the rate of basal tiller appearing on 15 cm stature post-pasture feature. Piatã grass managed at 25 cm developed smaller tiller amount on the second generation and greater tiller amount on the third generation than marandu grass. The greater tiller population density was observed on 25cm post-grazing pastures. There was no statistical difference of density between the two cultivars and between the cycles. Accordingly, it is concluded that piatã and marandu cultivars can be managed with 15cm and 25 cm post-grazing statures